Sex-specific foraging during parental care in a size-monomorphic seabird - Stefanie M Ismar; David Raubenheimer; Sarah Bury; Craig D Millar; Mark E Hauber (PANGAEA, 2016)
Sex differences in foraging behaviour are typically studied in size-dimorphic taxa. Data on sex-specific behavior in monomorphic taxa are needed to test theories of reproductive investment. It has been suggested that in seabirds foraging niche separation may be related to decreased intersexual competition for food between cooperating pair-bonded individuals. Alternatively, sex differences in foraging niches may be driven by different nutritional requirements of females associated with the reproductive costs of egg production and oviposition. To assess these possibilities, we studied a size-monomorphic colonial seabird, the Australasian Gannet (Morus serrator) at the Cape Kidnappers gannetry, New Zealand. We recorded maximum dive depths, and distinct diet composition of incubating females as indicated by stable isotopic signatures. Results suggested greater female foraging effort during early times of incubation, indicated by significantly deeper maximum dives. Sex-specific foraging patterns across other breeding stages were more variable. Nitrogen stable isotopic values showed that incubating females occupied a different trophic position compared to males at the same breeding stage, and also from those of gannets of both sexes at later stages of parental care. Overall, the data are consistent with cost-of-oviposition compensation in females necessitating male-bias in parental care in biparental breeders. Further research is needed to unravel the implications for the evolution of sex differences in behavior in this and other monomorphic taxa.
Supplement to: Ismar, SM et al. (2017): Sex-specific foraging during parental care in a size-monomorphic seabird, the Australasian Gannet (Morus serrator). Wilson Journal of Ornithology, 129(1), 139-147, https://doi.org/10.1676/1559-4491-129.1.139